Electric field distribution in 132 kV one piece premolded cable joint structures - Illias, Hazlee Azil; Lee, Z.H.; Bakar, A.H.A.; Mokhlis, Hazlie; Chen, G.; Lewin, P.L. (2012)
Defect in a cable joint is one of the main reasons of a power system being faulty. A defect can cause the electric field in the cable joint to become higher than the material surrounding the defect. This may result in partial discharge (PD) activity to occur within the defect site. When PD is repeating at the defect site, the material surrounding the defect will be affected, where PD may extend its path in the material. This may result in a breakdown at cable joint and consequently causes breakdown on the whole system. Therefore, the purpose of this research is to study the electric field distribution in 132 kV one piece premolded cable joint with and without the presence of defects. A better understanding of the electric field distribution at a cable joint can be attained by modelling the cable joint structure using finite element analysis (FEA) method. Through modelling and simulation results obtained in this work, an understanding of the electric field distribution in defects within cable joint structure can be enhanced.